2001
DOI: 10.1002/1522-2675(20010613)84:6<1227::aid-hlca1227>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Wechselwirkungen in Kristallen, 176. Mitteilung, Redox-Reaktionen von Hexahydropyren: Kristallstrukturen seiner Radikalanion-Salze sowie von Trihydropyrenylium-tetrachloroaluminat und Dichtefunktionaltheorie-Berechnungen

Abstract: Edgar Heilbronner zum 80. Geburtstag gewidmet Redox Reactions of Hexahydropyrene: Crystal Structures of Its Radical-Anion Salts as well as of Trihydropyrenylium Tetrachloroaluminate and Density-Functional-Theory CalculationsHexahydropyrene 1, a doubly propane-1,3-diyl-bridged peri-naphthalene derivative wtih 10 p-electrons allows both oxidation to its cation as well as reduction to its radical-anion salts, which could be crystallized and structurally characterized ± a rather rare case for small unsaturated hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…This composition differs from that reported by Kim et al for the electrochemically prepared GIC; they estimated the ratio of Na/diglyme as 1:1 and proposed a corresponding structure of the complex. However, the 2:1 molecule/Na ion ratio was also inferred from cyclic voltammograms examined by Jache et al, and several examples of stable [Na­(diglyme) 2 ] complexes are reported in crystal structures. Indeed, the optimized structure of a [Na­(diglyme) 2 ] complex, when calculated with a 6-31G basis set and Hartree–Fock method, has a diameter of 0.7–0.8 nm and therefore fits well into the expanded galleries of the GIC (0.84 nm). We therefore conclude that sodium ions in the GIC sample prepared in this research are coordinated by two diglyme molecules.…”
Section: Resultsmentioning
confidence: 92%
“…This composition differs from that reported by Kim et al for the electrochemically prepared GIC; they estimated the ratio of Na/diglyme as 1:1 and proposed a corresponding structure of the complex. However, the 2:1 molecule/Na ion ratio was also inferred from cyclic voltammograms examined by Jache et al, and several examples of stable [Na­(diglyme) 2 ] complexes are reported in crystal structures. Indeed, the optimized structure of a [Na­(diglyme) 2 ] complex, when calculated with a 6-31G basis set and Hartree–Fock method, has a diameter of 0.7–0.8 nm and therefore fits well into the expanded galleries of the GIC (0.84 nm). We therefore conclude that sodium ions in the GIC sample prepared in this research are coordinated by two diglyme molecules.…”
Section: Resultsmentioning
confidence: 92%